Sertularella maureenae, a new species of hydroid (Cnidaria: Hydrozoa: Sertulariidae) from the Pacific coast of Canada - Choong, Henry H. C.; Calder, Dale R.; Brinckmann-Voss, Anita (Zootaxa, 2012)
Sertularella maureenae, n. sp. (Hydrozoa: Sertulariidae), is described from the Pacific coast of Canada. The species is charac-terized by its predominantly stolonal colony form with pedicellate, annulated hydrothecae, together with the presence of large,ovate gonothecae having distinct annulations, a prominent neck, and 4–6 well-developed cusps surrounding the gonothecalaperture. The new species is compared to other stolonal species of the genus and to other typically erect species of Sertulariidaewith reported stolonal forms. The presence of both stolonal and semi–erect colony forms with pedicellate hydrothecae within S.maureenae, along with its hydrothecal characters, suggests that colony form alone may be an insufficient criterion for assigning species of pedicellate Sertularella with individual hydrothecae rising from their hydrorhizae to a separate genus Calamphora.